Pharmaceutical Analytical Study of Yashada Bhasma through Sem & Edx - Veda , S M; Medikeri, Surekha S; Vidya , Sagar G V (International Research Journal of Ayurveda & Yoga, 2023)
Yashada is a dhatu (metal) comes under pootiloha (metals with low melting point and burns with characteristic odor) its usage in bhasma (fine particles) form is prominently seen in the diseases like Prameha (Diabetes) Netrarogas (eye diseases) Vrana (wound) Kushta (skin diseases) etc. Raw Yashada (Metallic ore) was subjected to samanyashodhana (common purification process for metals), Visheshashodhana (special purification), Jarana (intermittent process of calcinations for pootilohas), Marana (incineration) followed by bhasmaparekshas (tests for proper calx) were done as mentioned in classical texts of Rasashastra and in each stage the product was subjected to SEM (Scanning Electron microscopy) & EDX (Energy dispersive X Ray) studies. Results showed Yashada bhasma was predominantly Zinc oxide with particle size reduction to about nano particle size and making the bhasma more bio-absorbable.